Relative age effect in elite sports: Methodological bias or real discrimination? - Delorme, N.; Boiche, J.; Raspaud, M. (European Journal of Sport Science, 2010)
Sport science researchers refer to a relative age effect when they observe a biased distribution of elite athletes' birth dates, with an over-representation of those born at the beginning of the competitive year and an under-representation of those born at the end. Based on the complete sample of French male licensed soccer players (n=1,831,524), we suggest that there could be an important bias in the statistical test of this effect. This bias could in turn lead to the false conclusion of systemic discrimination in the recruitment of professional players. Our findings question the accuracy of previous research on the existence of this effect in elite soccer.